Perbedaan Kecepatan Pengembangan Paru Sebelum dan Sesudah Latihan Pernapasan Diafragma dalam Upaya Mempercepat Pelepasan Water Seal Drainage (WSD) - Rosalina Rosalina; Sukarno Sukarno; Yunita Galih Yudanari (Universitas Ngudi Waluyo, 2019)
An Pleural effusion is an excessive accumulation of fluid, blood or water in thepleural cavity which will cause the increase of shortness of breath because of thedecreasing space for lung expansion. One of the efforts to reduce the complaintsof shortness of breath is by insertion of water seal drainage. Water Seal Drainage(WSD) is a medical action performed to remove air or fluid from the pleuralcavity. The patient's ability to breathe effectively is an indicator to release WSD.This study generally aims to determine the effectiveness of diaphragmaticbreathing exercises on the speed of lung expansion in patients with water sealdrainage insertion.The research design was pre experiment with pre test - post test group design.The population in this study were patients with insertion of WSD who wereadmitted to Dr. Muwardi Surakarta Hospital. The sampling technique waspurposive sampling. The number of samples were 16 respondents. To measurelung expansion, the indicator used Peak Expiratory Flow Rate as measured bypeak flow meter. Data analysis used dependent t-test.The results show that there are differences in the speed of lung expansion inpatients with WSD insertion before and after diaphragmatic breathing exerciseswith p-value of 0.0001.Suggestion for nurses to be able to train diaphragmatic breathing exercise inpatients with WSD insertion increase lung expansion so that WSD can bereleased and the risk of infection can be reduced